Dynamically Creating Tactical Network Emulation Scenarios using Unity and EMANE - Amato, Alessandro; Fronteddu, Roberto; Suri, Niranjan (MILCOM IEEE Military Communications Conference, 2023)
Modern tactical operations require collaboration between several communicating heterogeneous technologies which to perform adequately, must be tested in realistic environments. In this paper, we present a virtual testbed that leverages the physical capabilities of Unity 3D in conjunction with the EMANE network emulator to replicate a realistic network environment. Containerized applications can be tested within this environment to provide next-generation evaluation of their performance in realistic and customizable scenarios. Within this testbed, applications communicate through network links established using EMANE and grounded by an ad-hoc ray tracing propagation model. Finally, we compare our approach with equivalent solutions based on Matlab showing that we can achieve similar levels of fidelity and that our solution can be used for real-time testing.